Econometric evaluation of labour market policies - Lechner, Michael [Herausgeber]; Pfeiffer, Friedhelm [Herausgeber] (Physica-Verl., 2001)
Das Buch befasst sich mit der Thematik der empirischen Messung von Auswirkungen der aktiven Arbeitsmarktpolitik, die eine zentrale Aufgabe der Wirtschaftsforscher werden wird. Neue, verbesserte ökonometrische Methoden sind entwickelt worden, die auf zukünftige Forschungen in vielen Wirtschaftsbereichen Einfluss nehmen werden. Es werden die ökonometrischen Auswertungen der aktiven Arbeitsmarktprogramme aus Kanada, Frankreich, Italien, Slowakei, Schweden und der Bundesrepublik Deutschland veröffentlicht. Inhalt: HECKMAN/ VYTLACIL: Instrumental variables, selection models, and tight bounds on the average treatment effect; IMBENS: Some remarks on instrumental variables; LECHNER: Identification and estimation of causal effects of multiple treatments under the conditional independence assumption; BERGER/ BLACK/SMITH: Evaluating profiling as a means of allocation government services; BRODATY/CREPON/FOUGERE: Using matching estimators to evaluate alternative youth employment programs - Evidence from France (1986-1988); OURS: Do active labor market policies help unemployed workers to find and keep regular jobs ?; BATTISTIN/ GAVOSTO/RETTORE: Why do subsidised firms survive longer ? An evaluation of a program promoting youth entrepreneurship in Italy; HESHMATI/ENGSTRÖM: Estimating the effects of vocational rehabilitation programs in Sweden; LECHNER/PFEIFFER/SPENGLER/ ALMUS: The impact of non-profit temping agencies in individual labour market success. (BIBB)
Keywords: G 1.2 Arbeitsmarkt; I 2.3.2 Nordamerika; I 2.1 Deutschland; T 1.3 Systematische Berufsbildungsforschung; T 3 Forschungsmethoden; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; Empirische Forschung; Arbeitsmarktpolitik; Forschungsmethode; Evaluation; Ökonometrie; Quantitative Angaben; Kanada; Frankreich; Italien; Slowakei; Schweden